Male age and its association with reproductive traits in captive and wild house sparrows. (26th September 2019) - Girndt, Antje; Cockburn, Glenn; Sánchez‐Tójar, Alfredo; Hertel, Moritz; Burke, Terry; Schroeder, Julia
Abstract: Evolutionary theory predicts that females seek extra‐pair fertilizations from high‐quality males. In socially monogamous bird species, it is often old males that are most successful in extra‐pair fertilizations. Adaptive models of female extra‐pair mate choice suggest that old males may produce offspring of higher genetic quality than young males because they have proven their survivability. However, old males are also more likely to show signs of reproductive senescence, such as reduced sperm quality. To better understand why old males account for a disproportionally large number of extra‐pair offspring and what the consequences of mating with old males are, we compared several sperm traits of both captive and wild house sparrows, Passer domesticus . Sperm morphological traits and cloacal protuberance volume (a proxy for sperm load) of old and young males did not differ substantially. However, old males delivered almost three times more sperm to the female's egg than young males. We discuss the possibility of a post‐copulatory advantage for old over young males and the consequences for females mated with old males. Abstract : We found that old male house sparrows delivered almost three times more sperm to a female's egg than young males. Our result supports the observation that old males robustly gain more extra‐pair paternity, and we discuss the reproductive consequences for females mated with old males.